Interfacial, pore geometry and saturation effect on complex resistivity of shaly sandstone: dispersion and laboratory investigation - Khairy, Hilfan (Association of Korean Geoscience Societies and Springer, 2011)
The electrical evaluation of reservoir rock needs to deem several factors that really describe a subsurface condition. As confining pressure can cause either pore space of the rock to collapse or rock properties to change, a detailed identification towards the extent of the pressure and water saturation effect on electrical properties is needed. This work is mainly focused on the investigations of electrical properties on shaly sandstones, encompassing the effects of pore geometries, confining pressure, and partial water saturation on electrical properties. Here, the frequency of electrical measurement is between 1 Hz and 0.2 MHz. It is indicated that an interfacial and geometry change due to pressure is easily recognized by imaginary resistivity in low water saturation, reflecting that confining pressure will affect only small defect to pore geometry. Meanwhile in high water saturation, bulk volume conductivity is more dominant, thus making interfacial contribution negligible. From petrographic analysis of this work it is found that only pore radius distribution has a good relationship with electrical dispersion. The relaxation time and its distribution are estimated by simultaneous inversion of real and imaginary resistivity. The Cole-Cole model inversion is applied to obtain these parameters. For this purpose, the integration of Lavenberg-Marquardt and Singular Value decomposition (SVD) are used in order to avoid singularity problems. The obtainment of decreasing of relaxation time with the increasing of confining pressure reflects the reduction of the internal surface area.